Developing a Method for Evaluating the Comprehension of My Examples Using Spinning Whel by Applying to Students at Al- Qodiri Islamic Middle School Jember - Siti Alfiatul Jannah; Faisol Nasar Bin Madi; Abdur Rosid (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2024)
As we know, assessment is always used to measure students' abilities in all subjects. However, most schools use paper-based media to assess students' abilities, which allows students to cheat on each other. Therefore, the researcher aims to develop a spinning wheel-based assessment media for the Amtsilati textbook. The objectives of this research are 1) to describe the development of the student comprehension assessment towards "My Examples" using Spinney and Hill by applying to students at Qadri Islamic Intermediate School Jumber 2) To know the effectiveness of the product Developing the Student Comprehension Assessment towards "My Examples" using Spinney and Hill by applying to students at Qadri Islamic Middle School Jumber? The research method used in this study is research and development. The data used are qualitative and quantitative. The data collection techniques are interviews, observations, questionnaires, and tests. The population in this study is comprised of ninth-grade students with 30 samples. The results of this study are: 1) the researcher obtained the product's feasibility from two validation experts, namely instructional media experts and evaluation experts. The instructional media expert scored 77.23% with the criteria "good," while the evaluation expert gave a score of 97.84 with the criteria "excellent." 2) the effectiveness results are because 2.131 < 6.22 > 2.947, the researcher defines that t-count 6.22 is more significant than t-table at a significance level of 5% (0.05) for degrees of freedom 15 showing the number 2.131 at a significance level of 1% (0.01) showing the number 2.947. This indicates that the previous hypothesis can be accepted. Thus, the results of this study indicate that the development of assessment media is effective for student mastery in Amtsilati using the Spinning Wheel.Keywords : rating, spinney and hill, my examples